PERBEDAAN TINGKAT KECEMASAN MASA PUBERTAS ANTARA REMAJA PEREMPUAN DAN LAKI-LAKI DI SEKOLAH MADRASAH TSANAWIYAH N 1 PUNDONG BANTUL - Murgi Handari; Ika Mustika Dewi; Mey Candrawati (STIKES Wira Husada Yogyakarta, 2017)
Background: Anxiety is a mood disorder characterized by deep fears or concerns, while puberty is a phase that marked the maturity of the sexual organs and the achievement of reproductive ability, with the stages of puberty is referred to as the early stages of maturity while the age limit for laki- men 12-15 years and women 11-15 years old with the characteristics of primary and secondary sexual maturity that will continue to be driven by the level of anxiety experienced by children puberty. Objective: To determine differences in the level of anxiety of puberty in girls and boys in school MTs N 1 Pundong Bantul.Methods: The study was a comparative descriptive quantitative with cross sectional approach. Number of samples 49. Sampling technique is total sampling.Results: The level of anxiety puberty included in the category of anxiety was with adolescent girls 23 and boys 23 people so for a total of 46 people (93.9%), the Mann-Whitney U test according to the level of anxiety 26.45>23 52, we can see in the output test statistic, where the value of the test statistic Z is small at -1.709 and sig, 2-tailed is 0.088> 0.05, while for the exact sig ie 0.255> 0.05.Conclusion: The results of the study there was no difference in anxiety levels puberty in girls and boys in MTs school N 1 Pundong Bantul.